Aggressive combination chemotherapy of bone marrow relapse in childhood acute lymphoblastic leukemia containing aclacinomycin-A: a multicentric trial - Fengler, R; Buchmann, S; Riehm, H; Berthold, F; Dopfer, R; Graf, N; Holldack, J; Jobke, A; Jürgens, H; Klingebiel, T (Haematology and blood transfusion, 1987)
An intensive 7-day combination chemotherapy protocol was designed to reinduce children with early bone marrow relapse of acute lymphoblastic leukemia (less than 6 months after the end of or during preceding treatment). This aggressive approach seemed to be justified for a group of patients who were at the highest risk for ultimate treatment failure. In all, 38 children were enrolled for study. The ratio of male (median age, 10 years) to female (median age, 13 years) subjects was 27:11. Thirty patients were treated for their first relapse and eight for their second or subsequent relapse. Isolated bone marrow involvement was present in 24 cases. All patients had received heavy pretreatment including anthracyclines with cumulative doses of between 120 and 240 mg/m2. 22 of these patients, achieved complete remission, ten did not respond to therapy, and six died from the toxicity of the protocol. Cardiac failure was the cause of death in one child (after additional radiotherapy for a mediastinal mass). No further clinical manifestation of cardiomyopathy could be observed. The other five patients died from hemorrhages or infectious complications. The main side effects were fever, gastrointestinal problems, stomatitis, and severe bone marrow aplasia lasting for about 2 weeks with nadirs of platelets and white blood count around days 10-14. The remission rate of 60% was acceptable, though not satisfactory. Only four children survived disease-free for 13+, 14+, 20+, and 22+ months after diagnosis of relapse.